2008
DOI: 10.1590/s0100-29452008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest calcium sprays were not always needed to improve quality of 'gala' apples in Brazil

Abstract: -Calcium sprays have normally improved both the quality and the storage life of apples throughout the world because Ca helps to prevent many fruit disorders and that taken up from the soil does not often reach the fruit in adequate amounts. Since the efficacy of Ca sprays varies according to soil, apple cultivar, and weather conditions, this study was carried out from 1998 to 2004, in the Southern of Brazil, in order to assess the effect of Ca sprays on the quality and storability of 'Gala' fruits. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…Corroborating this result, Ernani et al (2008) also found that foliar calcium chloride application did not affect calcium concentration in the flesh of 'Gala' apples, in 5 of the 6 crop seasons assessed, despite spraying each crop 12 times. Neilsen & Neilsen (2002) evaluated the effect of preharvest foliar calcium chloride application of three apple cultivars ('Gala', 'Fuji' and 'Jonagold') grown in Canada and found a small increase in fruit calcium content, depending on the year, cultivar and number of applications.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Corroborating this result, Ernani et al (2008) also found that foliar calcium chloride application did not affect calcium concentration in the flesh of 'Gala' apples, in 5 of the 6 crop seasons assessed, despite spraying each crop 12 times. Neilsen & Neilsen (2002) evaluated the effect of preharvest foliar calcium chloride application of three apple cultivars ('Gala', 'Fuji' and 'Jonagold') grown in Canada and found a small increase in fruit calcium content, depending on the year, cultivar and number of applications.…”
Section: Methodsmentioning
confidence: 60%
“…For example, nine foliar applications of 0.6 % calcium chloride increased flesh firmness, reduced rottenness and lowered ethylene production in 'Fuji' apples stored for 9.5 months in a controlled atmosphere (1.2 kPa of O 2 and < 0.5 kPa of CO 2 ), at -0.5 ºC (Brackmann et al 2010). However, in five of the six crop seasons assessed, foliar application of 0.5 % calcium chloride showed no effect on bitter pit incidence, calcium concentration or flesh firmness in 'Gala' apples cold stored (-1ºC and 90-95 % RH) for five months, even with 12 foliar calcium sprays per season (Ernani et al 2008).…”
Section: Palavras-chavementioning
confidence: 83%
“…in addition, since the applied sulfate is not specifically adsorbed by the soil solid constituents, Ca mobility in the soil profile is high after applying this salt (ernani, 1986; ernani et al, 2001). accelerated leaching of mg (rosolem & machado, 1984;Caires et al, 2003Caires et al, , 2006ernani et al, 2006) andK (rosolem &machado, 1984;ernani et al, 2006) are some of the drawbacks of large gypsum applications to soils.…”
Section: De Profundidade) Enquanto Os De Mg Diminuíram Somente Namentioning
confidence: 99%
“…Apesar de intensa pesquisa em busca de medidas de controle, atualmente, a pulverização do pomar com cloreto de cálcio (CaCl 2 ; 0,4-0,6%) é o método mais utilizado para aumentar o teor de Ca no fruto e prevenir sua ocorrência. No entanto, em trabalho realizado com o objetivo de avaliar o efeito de diferentes números de pulverizações de CaCl 2 na cultura da macieira, não foi constada redução na incidência de "bitter pit" e/ou aumento no teor de Ca nas folhas e frutos (ERNANI et al, 2008). Desta forma, faz-se necessário o estudo de outras medidas, visando a aumentar os teores de Ca e a reduzir a incidência de "bitter pit" em maçãs.…”
Section: Introductionunclassified